Above‐ground biomass and vegetation attributes in the forest‐savannah mosaic of Togo, West Africa. (13th June 2020) - Atsri, Honam Komina; Kokou, Kouami; Abotsi, Komla Elikplim; Kokutse, Adzo Dzifa; Cuni‐Sanchez, Aida
Abstract: Despite the increasing interest in the role of African savannah and woodlands on the global carbon cycle, little is known about the above‐ground biomass (AGB) and the factors affecting it in these ecosystems in West Africa. We estimated AGB in different vegetation types of a forest–savannah mosaic in Togo, and we investigated the relationship between AGB, structural and diversity attributes. We also assessed the effects of using the ≥5 or ≥10 cm diameter threshold on AGB estimates. We sampled tree diameter, height and species of all trees ≥5 cm diameter following standardised protocols in 160 plots of 50 × 20 m (50 × 10 m for riparian). Above‐ground biomass (AGB) (all trees ≥5 cm diameter) ranged from 6.2 Mg/ha in shrub savannah to 292 Mg/ha in riparian forest and showed significant differences between vegetation types. Differences in AGB were related to structural attributes, with little influence of diversity attributes. The effects of minimum tree diameter size (5 or 10 cm) on AGB estimates were negligible. At a landscape level, closed‐canopy and open forests stored important quantities of carbon. We highlight the importance of the forest–savannah mosaic as a large carbon pool, which could be released if converted to another land cover type. Résumé: En dépit de l'intérêt croissant que suscite le rôle des savanes et des forêts claires africaines dans le cycle global du carbone, nous ne savons que peu de données sur la biomasse aérienne et les facteurs qui l'affectent dans ces écosystèmes en Afrique de l'ouest. Nous avons évalué la biomasse aérienne au sein de différents types de végétation dans une mosaïque de forêts et de savanes au Togo et nous avons étudié la relation entre les paramètres de structure et de diversité et la biomasse aérienne. Nous avons également évalué les effets de l'utilisation d'un seul de diamètre ≥ 5 ou ≥10 cm sur les estimations de la biomasse aérienne. Nous avons échantillonné les diamètres et les hauteursde tous les arbres d'un diamètre ≥ 5 cm en suivant des approches standardisées sur 160 parcelles de 50 x 20 m (50 x 10 m pour les forêts riveraines). La biomasse aérienne (tous les arbres d'un diamètre ≥5 cm) variait entre 6, 2 Mg ha ‐1 dans la savane arbustive et 292 Mg ha ‐1 dans la forêt riveraine, et les types de végétation présentaient des différences considérables. Les différences dans la biomasse aérienne étaient liées aux paramètres structuraux, alors que les attributs de diversité n'avaient que peu d'influence. Les effets de la taille minimum du diamètre des arbres (5 ou 10 cm) sur les estimations de la biomasse aérienne étaient négligeables. Au niveau du paysage, les forêts denses et les forêts claires stockent une quantité importante de carbone. Nous mettons en lumière l'importance de la mosaïque forêt‐savane en tant que grande réserve de carbone, qui pourrait être libéré en cas de conversion en un autre type d'utilisation des terres.